DEVELOPMENT OF NATURAL SCIENCE LEARNING INSTRUMENTS WITH CONTEXTUAL APPROACH USING PROBLEM SOLVING MODEL TO IMPROVE CRITICAL THINKING SKILL OF JUNIOR HIGH SCHOOL STUDENTS - Umar, Bahariyah; Jatmiko, Budi; Raharjo, Raharjo (Universitas Negeri Surabaya, 2018)
The aim of this research is to develop learning instruments of science through Contextual Approach using problem solving model which are reasonable to increase critical thinking skills of students. Learning Instruments are developed using 4-D model with one group pretest-posttest design. The Learning Instruments are tested at 74 students class VIII MTs Negeri Bonde Majene Regency West Sulawesi Province third semester 2016/ 2017 school Year for measuring application of lesson plan, hindrances during learning process, result of learning which is critical thinking skills of students, and respons of students to the learning instruments developed. Data Collection uses validation method, observation, testing, and questionnaires. The data of this research are analyzed quantitatively and qualitatively description. Finding of the research result, namely: (1) Instrument Validity including lesson Plan, Text book of students, activity sheets of students, test instruments of critical thinking indicated valid; (2) practically learning instruments are obtained from: (a) application of Lesson plan categorized by 95.23% with excellent category, and (b) obstacles during learning process; and (3) affectivity of learning instruments in terms of : (a) critical thinking skills of students through n-gain with higher category over 0.7 (Hake, 1999), and (b) the respons of students to the instruments and application of learning are very good. Based on the result of data analysis, can be concluded that learning instruments of science through Contextual Approach using problem solving model are feasible to increase critical thinking skills of students.